Prevalence and Infection’s Degree of Gastrointestinal Nematode Worm in Friesian Holstein Dairy Cows at KUTT Suka Makmur Pasuruan Regency - Utami, Kinanti Putri; Santoso, Kuncoro Puguh; Suwanti, Lucia Tri; Hastutiek, Poedji; Permatasari, Dian Ayu; Sunarso, Agus (Universitas Airlangga, 2024)
This study aims to determine the type, prevalence, and infection’s degree of gastrointestinal Nematode worm in Friesian Holstein Dairy Cows at KUTT Suka Makmur, Pasuruan Regency. The study was conducted in July – September 2023. One hundred of feces samples were collected from four districts at KUTT Suka Makmur working area. Samples were examined by sedimentation and floating methods. Positive samples were further examined by McMaster methods to determine the number of worm eggs per gram feces. The type of worms were Oesophagostomum sp. (24%), Haemonchus sp. (20%), Mecistocirrus sp. (13%), Trichuris sp. (8%), Ostertagia sp. (6%), Trichostrongylus sp. (6%), Nematodirus sp. (3%), and Strongyloides sp. (3%). The prevalence of gastrointestinal Nematode worm was 66% with mild and severe degrees of infection. The Chi Square test results showed that age had no effect on the prevalence and infection’s degree of gastrointestinal Nematode worm in Friesian Holstein dairy cows at KUTT Suka Makmur. While location had effect on the prevalence but had no effect on the infection’s degree.